ANALISIS STRUKTUR BATIN PUISI “HUJAN BULAN JUNI” KARYA SAPARDI DJOKO DAMONO - astriani indah pratiwi; ika mustika; indra permana (IKIP Siliwangi, 2020)
Poetry as one type of literary work consisting of a series of words and contain meaning. Therefore, to understand poetry it is necessary to have an in-depth study. Researchers chose June Rain's poetry as the object of poetry to be analyzed. June rain poetry uses a variety of languages so as to produce deep meaning for the reader. The formulation of the problem in this study is What is the inner structure contained in the June rain poem ?. The purpose of this research is to describe the inner structure contained in the June rain poem. The research method in this study is a structural approach that aims to find out and describe the inner structure contained in the poem. Data analysis techniques in this research are poetry reading, analyzing the inner structure of pusii and giving conclusions. The results of the poetry analysis contain the theme of love and approach to have a feeling or a moving atmosphere because of the sincerity of his love and have a tone that tends to be low and calm emotions and have a mandate so that every human being has the character of being stoic, wise and discerning. Keywords: Analysis, Inner Structure, Poetry